2017
DOI: 10.1302/1863-2548.11.170107
|View full text |Cite
|
Sign up to set email alerts
|

Clinically apparent adverse reactions to intra-wound vancomycin powder in early onset scoliosis are rare

Abstract: PurposeSpine surgeons have increasingly used intraoperative application of topical vancomycin powder (TVP) to prevent surgical site infections (SSIs). The goals of this study were to define the rate of pharmacological adverse reaction to TVP in young patients undergoing posterior spinal surgery and to summarise institutional variation in TVP dosing.MethodsThis retrospective observational study included ten spine centres in the United States and one in Europe. Patients with early onset scoliosis who underwent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…61 A recent systematic review of DeFrancesco et al found only one case of adverse drug reaction (transient rash) in almost 1400 children undergoing posterior spinal surgery for early onset scoliosis, a rate of only 0.072%. 62 In addition, patients in this study that had previously shown adverse drug reactions to intravenous vancomycin did not react to intrawound vancomycin powder. Nonunion of bone is another potential complication of local antibiotics at high concentrations.…”
Section: Complications and Adverse Eventsmentioning
confidence: 72%
“…61 A recent systematic review of DeFrancesco et al found only one case of adverse drug reaction (transient rash) in almost 1400 children undergoing posterior spinal surgery for early onset scoliosis, a rate of only 0.072%. 62 In addition, patients in this study that had previously shown adverse drug reactions to intravenous vancomycin did not react to intrawound vancomycin powder. Nonunion of bone is another potential complication of local antibiotics at high concentrations.…”
Section: Complications and Adverse Eventsmentioning
confidence: 72%
“…[ 37 , 38 ] Based on this, we and other authors therefore encourage more clinical trials for lower doses of intrawound vancomycin. [ 39 , 40 ] The use of intrawound vancomycin may increase the incidence of gram-negative and polymicrobial postoperative infections in our study; however, it is under debate in the literature. [ 41 ] BMI showed an association in our study with wound infection and dehiscence, which is consistent with the findings in the literature of an increased incidence of wound complications with higher BMI.…”
Section: Discussionmentioning
confidence: 94%
“…Intrawound vancomycin in pediatric spine surgeries has been considered relatively safe in the pediatric age group as well. A 2017 study by the Children’s Spine Study Group reviewed 1,398 patients and reported only 1 possible adverse reaction in the form of rash without any systemic effects 19,20 . All the reports of adverse reactions are in adults with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%